Active Vibration Control of Pipe-Shaped Robot Arm - PATER, Marcin Adam; LENIOWSKA, Lucyna; GROCHOWINA, Marcin (Engineering Transactions, 2024)
Robotic systems, because of their construction, are susceptible to vibrations that significantly affect their accuracy. Consequently, many efforts are made to eliminate vibrations and stabilize the structure as effectively as possible through the use of various solutions. This article presents the results of research on the use of piezoelectric elements- micro fiber composite (MFC) to reduce vibrations in a thin-walled tube, serving as a model of a lightweight robot arm. The aim of the research is to develop an effective method for vibration cancelation of considered arm model. In our approach, MFC elements were used to perform dual roles: as sensors and actuators. The object model was obtained based on measurements taken on a laboratory stand using an acquisition card and the xPC Target (Matlab) environment. Based on the obtained data, an ARX-type model was developed, and an optimal controller was selected for application in the designed active vibration reduction system. The article includes the results of tests carried out for several different vibration-inducing signals, confirming the effectiveness of the applied vibration-reduction method.